Cyclometallated Palladium(II) Complexes: An Approach to the First Dinuclear Bis(iminophosphorane)phosphane-[C,N,S] Metallacycle - Marcos Rúa-Sueiro; Paula Munín-Cruz; Adolfo Fernández; Juan M. Ortigueira; María Teresa Pereira; José M. Vila (Molecules, 2022)
Treatment of bis(iminophosphorane)phosphane ligands 2a–2e with Li2PdCl4 gave a set of novel diphosphane-derived complexes bearing two metallacycle rings, each one enclosing a P=N double bond: the unprecedented bis(iminophosphorane)phosphane-[C,N,S] palladacycles. In the case of the ligand derived from bis(diphenylphosphino)methane, 2a, both the single and the double palladacycle complexes were obtained. Reaction of 3a with bis(diphenylphosphino)ethane did not yield the expected product with the diphosphane bonded to both palladium atoms, but rather the novel coordination compound 5. The crystal structures of 3c and 5 are described.